Potential Impact of Global Warming on Virus Propagation in Infected Plants and Agricultural Productivity - Amari, Khalid; Huang, Caiping; Heinlein, Manfred (Frontiers in Plant Science, 2021)
The increasing pace of global warming and climate instability will challenge the management of pests and diseases of cultivated plants. Several reports have shown that increases in environmental temperature can enhance the cell-to-cell and systemic propagation of viruses within their infected hosts. These observations suggest that earlier and longer periods of warmer weather may cause important changes in the interaction between viruses and their hosts plants, thus posing risks of new viral diseases and outbreaks in agriculture and the wild. As viruses target plasmodesmata for cell-to-cell spread, these cell wall pores may play yet unknown roles in the temperature-sensitive regulation of intercellular communication and virus infection. Understanding the temperature-sensitive mechanisms in plant-virus interactions will provide important knowledge for protecting crops against diseases in a warmer climate.